2017
DOI: 10.3382/ps/pew356
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between xylanase and phytase on the digestibility of corn and a corn/soy diet for broiler chickens

Abstract: An experiment was carried out to evaluate the digestibility and metabolizability of corn and a corn/soy-based diet with the inclusion or not of xylanase and/or phytase in broilers. In the trial, 1,120 broiler chicks were distributed according to a completely randomized experimental design, consisting of 16 treatments, with 10 replicates of 7 birds each. Treatments were evaluated following a factorial arrangement (4 × 2 × 2), with 4 xylanase levels (zero, 50, 100, or 150 fungal β-xylanase units/kg; FXU), 2 phyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
1
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 18 publications
1
11
1
3
Order By: Relevance
“…Juanpere et al (2005) indicated that on top supplementation of multi-carbohydrase increases nutrients digestibility when added to barley-SBM diets containing phytase, although they have not observed more beneficial outcomes when multi-carbohydrase supplemented to phytase containing C-SBM diets. However, the current results are in contrast with the findings of Schramm et al (2017) who reported that total tract digestibility of DM and energy and ileal digestibility of CP increased by on top supplementation of multi-carbohydrase to C-SBM diets containing phytase. Kocher et al (2003) observed that the combined addition of pectinase, protease, and amylase increased AMEn when added to C-SBM diets with reduced energy and protein density.…”
Section: Digestibilitycontrasting
confidence: 99%
“…Juanpere et al (2005) indicated that on top supplementation of multi-carbohydrase increases nutrients digestibility when added to barley-SBM diets containing phytase, although they have not observed more beneficial outcomes when multi-carbohydrase supplemented to phytase containing C-SBM diets. However, the current results are in contrast with the findings of Schramm et al (2017) who reported that total tract digestibility of DM and energy and ileal digestibility of CP increased by on top supplementation of multi-carbohydrase to C-SBM diets containing phytase. Kocher et al (2003) observed that the combined addition of pectinase, protease, and amylase increased AMEn when added to C-SBM diets with reduced energy and protein density.…”
Section: Digestibilitycontrasting
confidence: 99%
“…However, these products contain considerable amounts of NSPs, such that using carbohydrases may have a positive impact on animal performance. Schramm et al (2017) affirmed that the presence of phytase, in a complete corn/soy-based diet, has a potentiating effect for exogenous xylanase. In our study, the performance results were improved in broilers fed diets containing nutritional reductions and enzymatic supplementation with carboydrases, showed the action of this enzyme.…”
Section: Performancementioning
confidence: 86%
“…Toledo et al (2007) support this result in a study that evaluated the enzyme complex supplementation of broiler diets up to 35 days of age, verifying that birds require higher metabolizable energy due to lower digestive capacity. Similarly, Yang et al (2010) and Schramm et al (2016) attributed the inefficacy of exogenous enzymes to nutritional imbalance, which inhibits the activity of enzymes that improve nutrient degradation, digestion, and absorption.…”
Section: Resultsmentioning
confidence: 99%
“…However, the existing knowledge about the role of enzymes is limited, controversial, or inconsistent, demonstrating that information is still needed in this area of research (OLUKOSI et al, 2007;JIANG et al, 2008;CARDOSO et al, 2011;AMERAH et al, 2016;SCHRAMM et al, 2016).…”
Section: Introductionmentioning
confidence: 99%